Personal Knowledge Management, Leadership Styles, and Organisational Performance: A Case Study of the Healthcare Industry in Thailand - Zumitzavan, Vissanu (Springer, 2016)
This book presents unique management perspectives from Thailand’s Healthcare Industry. It focuses on the areas of Personal Knowledge Management, Leadership Styles and Organisational Performance. The book highlights the various business challenges that organisations face in the context of globalisation, which itself has produced new opportunities and difficulties alike. In addition, it also elaborates on how even large organisations with strong histories can no longer compete unless they are willing to adapt to changing conditions. Demonstrating how transferring and encouraging knowledge within an organisation can generate approaches that promote its continuing success, the book mainly focuses on the perspective of the Resource Based View, a broadly recognised method for maintaining the competitive advantages of an organisation. It also stresses the importance of making the most use of organisational resources. The book offers a valuable reference work, not only for practitioners and academic researchers in the fields of Business & Management but also for students taking Leadership Management, Organisational Learning and Organisational Performance Appraisal courses, serving as a sourcebook for the principles of successful management.